Citizen Spielberg - Friedman, Lester D. (University of Illinois Press, 2022)
"Steven Spielberg's extraordinary career redefined Hollywood, but his achievement goes far beyond shattered box office records. Rejecting the view of Spielberg as a Barnumesque purveyor of spectacle, Lester D. Friedman presents the filmmaker as a major artist who pairs an ongoing willingness to challenge himself with a widely recognized technical mastery. This new edition of Citizen Spielberg expands Friedman's original analysis to include films of the 2010s like Lincoln and Ready Player One. Breaking down the works by genre, Friedman looks at essential aspects of Spielberg's art, from his storytelling concerns and worldview to the uncanny connection with audiences that has powered his longtime influence as a cultural force. Friedman's examination reveals a sustained artistic vision--a vision that shows no sign of exhausting itself or audiences after Spielberg's nearly fifty years as a high-profile filmmaker. Incisive and discerning, Citizen Spielberg, Second Edition, offers a career-spanning appraisal of a moviemaking icon"--